Differences in phyllosphere microbiomes among different Populus spp. in the same habitat - Liu, Jiaying; Zhang, Weixi; Liu, Yuting; Zhu, Wenxu; Yuan, Zhengsai; Su, Xiaohua; Ding, Changjun (Frontiers in Plant Science, 2023)
The above-ground parts of terrestrial plants are collectively known as the phyllosphere. The phyllosphere is one of the richest habitats in which microbiota colonize. The surface of the leaf blade is a unique and extensive habitat for microbial communities. Phyllosphere bacteria are the second most closely associated microbial group with plants after fungi and viruses, and are the most abundant, occupying a dominant position in the phyllosphere microbial community. Host species are a major factor influencing the community diversity and structure of phyllosphere microorganisms. In this study, six Populus spp. were selected for study under the same site conditions and their phyllosphere bacterial community DNA fragments were paired-end sequenced using 16S ribosomal RNA (rRNA) gene amplicon sequencing. Based on the distribution of the amplicon sequence variants (ASVs), we assessed the alpha-diversity level of each sample and further measured the differences in species abundance composition among the samples, and predicted the metabolic function of the community based on the gene sequencing results. The results revealed that different Populus spp. under the same stand conditions resulted in different phyllosphere bacterial communities. The bacterial community structure was mainly affected by the carbon and soluble sugar content of the leaves, and the leaf nitrogen, phosphorus and carbon/nitrogen were the main factors affecting the relative abundance of interleaf bacteria. This study provides theoretical support for the study of the composition and structure of phyllosphere bacterial communities in woody plants and the factors influencing them.